2019
DOI: 10.1021/acsnano.9b06395
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Responsive Nanoparticles for Rapid and Extended Self-Regulated Insulin Delivery

Abstract: To mimic native insulin activity, materials have been developed that encapsulate insulin, glucose oxidase, and catalase for glucose-responsive insulin delivery. A major challenge, however, has been achieving the desired kinetics of both rapid and extended release. Here, we tune insulin release profiles from polymeric nanoparticles by altering the degree of modification of acid-degradable, acetalated-dextran polymers. Nanoparticles synthesized from dextran with a high acyclic acetal content (94% of residues) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 45 publications
5
90
0
Order By: Relevance
“…This enables delivery of various payloads including hydrophobic and hydrophilic compounds, as well as cargos with different molecular weights such as small molecules, biological macromolecules, proteins and vaccines [30][31][32][33][34][35] , making polymeric NPs ideal for co-delivery applications 36 . By modulating properties such as composition, stability, responsivity and surface charge, the loading efficacies and release kinetics of these therapeutics can be precisely controlled 37,38 .…”
Section: Polymeric Npsmentioning
confidence: 99%
“…This enables delivery of various payloads including hydrophobic and hydrophilic compounds, as well as cargos with different molecular weights such as small molecules, biological macromolecules, proteins and vaccines [30][31][32][33][34][35] , making polymeric NPs ideal for co-delivery applications 36 . By modulating properties such as composition, stability, responsivity and surface charge, the loading efficacies and release kinetics of these therapeutics can be precisely controlled 37,38 .…”
Section: Polymeric Npsmentioning
confidence: 99%
“…The response to the pH change is a volume transition of the polymer, and in this manner, the body's glucose level is driven by conformational polymer changes [115]. Some authors synthesized acetalated dextran nanoparticles or acryloyl cross-linked dextran dialdehyde (ACDD) nanocarriers containing enzymes and insulin to facilitate glucose-sensitive release [103,116]. Boronic acid-derived hydrogels were used to obtain glucosesensitive platforms for drug delivery [104,117].…”
Section: Glucose-responsive Nanomaterialsmentioning
confidence: 99%
“…FrĂ©chet et al also reported facile synthesis of acid-responsive materials by acetalation of dextran using 2-methoxypropene or other functional molecules [ [163] , [164] , [165] ]. Thus obtained acetalated dextran polymers have been examined for encapsulation and pH-triggerable release of small molecules, nucleotides, and proteins in the forms of nanoparticles or microparticles [ 164 , [166] , [167] , [168] , [169] ]. Our group demonstrated that kinetically controlled acetalation can be carried out for cyclic oligosaccharides, such as α-CD, ÎČ-CD, and their polymers, thereby affording a series of acid-labile biocompatible materials [ 170 , 171 ].…”
Section: Materials and Delivery Vehicles Responsive To Inflammatory Smentioning
confidence: 99%